MORPHOLOGY AND MORPHOMETRY CHARACTERISTIC OF RAYA WATERSHED - Kurzah, Muhammad Yusril Ihza; Nurhayati, Nurhayati; Yulianto, Eko (Jurnal Teknik Sipil, 2024)
The study of watershed morphology and land use patterns significantly affects hydrological processes and runoff coefficients, highlighting the quantitative nature of watershed characteristics. The Raya Watershed in West Kalimantan influences local communities and aims to enhance understanding of its physical attributes and hydrological dynamics through detailed analysis of topography, soil composition, land use, and river networks. Findings inform watershed management and conservation strategies. The analysis of the Raya Watershed, spanning 29,982.96 hectares (87.34% of total area) with elevations below 100 meters, reveals flat terrain vulnerable to flooding, particularly in low-lying or sea-level regions, exacerbated by limited natural drainage. Lower elevations support crucial wetland and floodplain ecosystems. Hydrological disruptions from land use changes and climate fluctuations can harm biodiversity and water quality. Effective land use planning is vital to address flood risk and environmental concerns, mitigating impacts like property damage and population displacement. Soil-type mapping informs conservation efforts, ensuring ecosystem resilience. Sustainable land management practices, guided by watershed characteristics like drain density and stream frequency, are essential to mitigate biodiversity loss and ecological imbalances.